Comparison of perioperative radiation therapy and surgery versus surgery alone in 204 patients with primary retroperitoneal sarcoma: a retrospective two-institution study - Kelly, Kaitlyn J. (Ann Surg, 2015)
OBJECTIVE: To compare outcomes of patients with retroperitoneal or pelvic sarcoma (RPPS) treated with versus without perioperative radiation therapy (RT). SUMMARY BACKGROUND DATA: Radiation therapy for RPPS is controversial, and few studies have compared outcomes with and without RT. METHODS: Prospectively-maintained databases were reviewed to retrospectively compare patients with primary RPPS treated during 2003-2011. Multivariate Cox regression models were used to assess associations with the primary endpoints: local recurrence-free survival (LRFS) and disease-specific survival (DSS). RESULTS: At one institution 172 patients were treated with surgery alone while at another institution 32 patients were treated with surgery and perioperative proton beam RT or intensity-modulated RT with or without intraoperative RT. The groups were similar in age, tumor size, grade, and margin status (all p>0.08). The RT group had a higher percentage of pelvic tumors (p=0.03) and a different distribution of histologies (p=0.04). Perioperative morbidity was higher in the RT group (44% vs 16% of patients; p=0.004). After a median follow-up of 39 months, 5-year LRFS was 91% (95% CI, 79-100%) in the RT group and 65% (57-74%) in the surgery only group (p=0.02). On multivariate analysis, RT was associated with better LRFS (hazard ratio 0.26; p=0.03). Five-year DSS was 93% (95% CI, 82-100%) in the RT group and 85% (78-92%) in the surgery-only group (p=0.3). CONCLUSIONS: The addition of advanced-modality RT to surgery for primary RPPS was associated with improved LRFS, although this did not translate into significantly better DSS. This treatment strategy warrants further investigation in a randomized trial.